Duration of breast feeding and language ability in middle childhood - Whitehouse, A.; Robinson, M.; Li, Jianghong; Oddy, W. (Wiley-Blackwell Publishing Ltd., 2011)
Duration of breast feeding and language ability in middle childhood 1. Andrew J. O. Whitehouse1,2,*, 2. Monique Robinson1, 3. Jianghong Li1,3, 4. Wendy H. Oddy1Article first published online: 25 OCT 2010DOI: 10.1111/j.1365-3016.2010.01161.x© 2010 Blackwell Publishing Ltd.IssuePaediatric and Perinatal EpidemiologyPaediatric and Perinatal EpidemiologyVolume 25, Issue 1, pages 44–52, January 2011Additional Information(Show All)How to CiteAuthor InformationPublication HistoryHow to CiteWhitehouse, A. J. O., Robinson, M., Li, J. and Oddy, W. H. (2011), Duration of breast feeding and language ability in middle childhood. Paediatric and Perinatal Epidemiology, 25: 44–52. doi: 10.1111/j.1365-3016.2010.01161.xAuthor Information 1. 1 Telethon Institute for Child Health Research, Centre for Child Health Research 2. 2 Neurocognitive Development Unit, School of Psychology, The University of Western Australia 3. 3 Centre for Developmental Health, Curtin Health Innovation Research Institute, Curtin University of Technology, Perth, Western Australia, Australia*Correspondence: Andrew J. O. Whitehouse,*Correspondence: Dr Andrew Whitehouse, Telethon Institute for Child Health Research, Centre for Child Health Research, The University of Western Australia, West Perth, Western Australia 6872, Australia. E-mail: awhitehouse@ichr.uwa.edu.auPublication History 1. Issue published online: 7 DEC 2010 2. Article first published online: 25 OCT 2010SEARCHSearch ScopeSearch String * Advanced > * Saved Searches >SEARCH BY CITATIONVolume:Issue:Page:ARTICLE TOOLS * Get PDF (133K) * Save to My Profile * E-mail Link to this Article * Export Citation for this Article * Get Citation Alerts * Request Permissions * Abstract * Article * References * Cited ByView Full Article (HTML) Get PDF (133K)Keywords: * breast feeding; * language development; * Raine StudySummaryWhitehouse AJO, Robinson M, Li J, Oddy WH. Duration of Breast feeding and language ability in middle childhood. Paediatric and Perinatal Epidemiology 2010.There is controversy over whether increased breast-feeding duration has long-term benefits for language development. The current study examined whether the positive associations of breast feeding on language ability at age 5 years in the Western Australian Pregnancy (Raine) Cohort, were still present at age 10 years. The Raine Study is a longitudinal study of 2868 liveborn children recruited at approximately 18 weeks gestation. Breast-feeding data were based upon information prospectively collected during infancy, and were summarised according to four categories of breast-feeding duration: (1) never breast-fed, (2) breast-fed predominantly for <4 months, (3) breast-fed predominantly for 4–6 months, and (4) breast-fed predominantly for >6 months. Language ability was assessed in 1195 children at the 10 year follow-up (mean age = 10.58 years; standard deviation = 0.19) using the Peabody Picture Vocabulary Test – Revised (PPVT-R), which is based around a mean of 100 and a standard deviation of 15. Associations between breast-feeding duration and PPVT-R scores were assessed before and after adjustment for a range of sociodemographic, obstetric and psychosocial covariates. Analysis of variance revealed a strong positive association between the duration of predominant breast feeding and PPVT-R at age 10 years. A multivariable linear regression analysis adjusted for covariates and found that children who were predominantly breast-fed for >6 months had a mean PPVT-R score that was 4.04 points higher than children who were never breast-fed. This compared with an increase of 3.56 points at age 5 years. Breast feeding for longer periods in early life has a positive and statistically-independent effect on language development in middle childhood.View Full Article (HTML) Get PDF (133K)More content like thisFind more content: * like this articleFind more content written by: * Andrew J. O. Whitehouse * Monique Robinson * Jianghong Li * Wendy H. Oddy * All Author